Live and pasteurized Akkermansia muciniphila decrease susceptibility to Salmonella Typhimurium infection in mice - Jiaxiu Liu; Hongli Liu; Huanhuan Liu; Yue Teng; Ningbo Qin; Xiaomeng Ren; Xiaodong Xia (Journal of Advanced Research, 2023)
Introduction: The gut microbiome is vital for providing resistance against colonized pathogenic bacteria. Recently, specific commensal species have become recognized as important mediators of host defense against microbial infection by a variety of mechanisms. Objectives: To examine the contribution of live and pasteurized A. muciniphila to defend against the intestinal pathogen Salmonella Typhimurium in a streptomycin-treated mouse model of infection. Methods: C57B6J mice were pretreated with phosphate-buffered saline (PBS), live Akkermansia muciniphila (AKK), and pasteurized A. muciniphila (pAKK) for two weeks, then mice were infected by S. Typhimurium SL 1344. 16S rRNA-based gut microbiota analysis was performed before and after infection. Bacterial counts in feces and tissues, histopathological analysis, gut barrier-related gene expression, and antimicrobial peptides were examined. Co-housing was performed to examine the role of microbiota in the change of susceptibility of mice to infection. Results: AKK and pAKK markedly decreased Salmonella fecal and systemic burdens and reduced inflammation during infection. Notably, further characterization of AKK and pAKK protective mechanisms revealed different candidate protective pathways. AKK promoted gut barrier gene expression and the secretion of antimicrobial peptides, and co-housing studies suggested that AKK-associated microbial community played a role in attenuating infection. Moreover, pAKK had a positive effect on NLRP3 in infected mice. We verified that pretreatment of pAKK could promote the expression of NLRP3, and enhance the antimicrobial activity of macrophage, likely through increasing the production of reactive oxygen (ROS), nitric oxide (NO), and inflammatory cytokines. Conclusion: Our study demonstrates that live or pasteurized A. muciniphila can be effective preventive measures for alleviating S. Typhimurium-induced disease, highlighting the potential of developing Akkermansia-based probiotics or postbiotics for the prevention of Salmonellosis.